2021
DOI: 10.3389/fonc.2021.670156
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative T2*-Weighted Imaging and Reduced Field-of-View Diffusion-Weighted Imaging of Rectal Cancer: Correlation of R2* and Apparent Diffusion Coefficient With Histopathological Prognostic Factors

Abstract: PurposeTo assess T2*-weighted imaging (T2*WI) and reduced field-of-view diffusion-weighted Imaging (rDWI) derived parameters and their relationships with histopathological factors in patients with rectal cancer.MethodsFifty-four patients with pathologically-proven rectal cancer underwent preoperative T2*-weighted imaging and rDWI in this retrospective study. R2* values from T2*-weighted imaging and apparent diffusion coefficient (ADC) values from rDWI were compared in terms of different histopathological progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The quantitative T2 relaxation time is widely used in the brain, breast, kidney, and prostate (16,(25)(26)(27). The R2* value was also closely related to histopathological prognostic factors in RC by T2*-weighted imaging (28), which was consistent with the present result. Previous results on the association between T2 value and prognosis factors in other diseases have been consistent (24,27,29).…”
Section: Discussionsupporting
confidence: 91%
“…The quantitative T2 relaxation time is widely used in the brain, breast, kidney, and prostate (16,(25)(26)(27). The R2* value was also closely related to histopathological prognostic factors in RC by T2*-weighted imaging (28), which was consistent with the present result. Previous results on the association between T2 value and prognosis factors in other diseases have been consistent (24,27,29).…”
Section: Discussionsupporting
confidence: 91%
“…R2* has been found to reflect the liver iron content and tumor hypoxia of breast cancer ( 33 , 34 ). Previous reported ( 14 , 15 ) demonstrated that R2* correlated with the status of deoxyhemoglobin and blood oxygenation, with the increased level of blood deoxyhemoglobin could potentially leading to elevated R2* ( 35 ). Tumors with advanced stage lead to a more hypoxic microenvironment due to the rapid proliferation of tumor cells and tumor development ( 36 , 37 ), resulting in increased content of deoxyhemoglobin and R2* values.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, diffusion-weighted imaging (DWI) is often used for the preoperative assessment of TNM (Tumor Node Metastasis) staging of rectal adenocarcinoma and is helpful for the discrimination of histological prognostic factors. However, DWI often fails to distinguish some histological features (15,16). Furthermore, previous studies suggest that apparent diffusion coefficient (ADC) measurements from DWI are not consistent with the utility of different b values (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi echo T2*w imaging is a method that visualizes endogenous paramagnetic deoxyhemoglobin, which in breast cancer has been shown to correlate to tumor hypoxia [14] . In rectal cancer, the method has recently shown potential to provide a useful quantitative biomarker [15] .…”
Section: Introductionmentioning
confidence: 99%